1999
DOI: 10.1128/iai.67.5.2209-2217.1999
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin 1 fromEscherichia coliBlocks Activation and Proliferation of Bovine Lymphocyte Subpopulations In Vitro

Abstract: Shiga toxin-producing Escherichia coli (STEC) is widespread in the cattle population, but the clinical significance of Shiga toxins (Stx’s) for the bovine species remains obscure. Since Stx’s exert immunomodulating effects in other species, we examined the effect of purified Stx1 on a bovine B lymphoma cell line (BL-3) and peripheral blood mononuclear cells (PBMC) isolated from adult bovine blood by viability assays and flow cytometry analysis. Stx1 markedly induced apoptosis in stimulated BL-3 cells. The susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 50 publications
2
51
2
Order By: Relevance
“…The high prevalence of STEC, EPEC, and EHEC in healthy and diarrheic animals shows, that these animals can be considered as reservoirs for human pathogenic E. coli. The role of STEC, EPEC, and EHEC as causative agents of diarrhea in calves have been widely investigated (Dean-Nystrom et al, 1998;Menge et al, 1999;Pruimboom-Brees et al, 2000;Hoey et al, 2002). Lack of Stx receptor in vascular endothelium makes cattle a perfect candidate as a reservoir of STEC/EHEC as it is not possible for them to develop systemic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of STEC, EPEC, and EHEC in healthy and diarrheic animals shows, that these animals can be considered as reservoirs for human pathogenic E. coli. The role of STEC, EPEC, and EHEC as causative agents of diarrhea in calves have been widely investigated (Dean-Nystrom et al, 1998;Menge et al, 1999;Pruimboom-Brees et al, 2000;Hoey et al, 2002). Lack of Stx receptor in vascular endothelium makes cattle a perfect candidate as a reservoir of STEC/EHEC as it is not possible for them to develop systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of Stx receptor in vascular endothelium makes cattle a perfect candidate as a reservoir of STEC/EHEC as it is not possible for them to develop systemic disease. Other actions of STEC/EHEC like immunomodulation (Menge et al, 1999) and intestinal colonization (Etcheverría and Padola, 2013) help them to survive and propagate in the host intestine. Major questions remain to be answered as to whether these processes contribute to pathogenesis of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to previous studies in which stx 1 -positive STEC has been more frequently associated with diarrhoeic calves than stx 2 -positive STEC (Wieler et al, 1996), we have found that the majority (80.0%) of the STEC strains recovered harboured the stx 1 gene. Recently, Menge et al (1999) have reported that Stx1 seems to contribute to the pathogenesis of STEC-associated diarrhoea in calves by suppressing the mucosa-associated immune response. Otherwise, epidemiological studies suggested that patients with the most severe forms of the disease, including renal and extra-renal symptoms, were generally infected with Stx1-Stx2-producing or Stx2-producing E. coli (Scotland et al, 1987;Lo´pez et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide by mitochondrial enzymes in viable cells (Menge et al, 1999). The cellular metabolic activity was not affected by telithromycin in a concentration range from 2.5 to 10 mg mL À1 even when the cells were incubated with the ketolide for 24 h (data not shown).…”
Section: Effects Of Telithromycin On the Cytokine And No Production Bmentioning
confidence: 86%